Creative writing analysis - Harper, Graeme (Routledge, an imprint of the Taylor & Francis Group, 2023)
"All creative writers engage in forms of analysis. That is, we engage in detailed examinations of subjects and themes, of ways of approaching the writing of a single poem or an entire book of poems, of writing a novel or a screenplay. Analysis for creative writers often comes naturally and is frequent. When we reach an understanding of the types of analysis that are available to us, and the forms of analysis we employ, we have more tools at our disposal to progress a project or to find solutions to creative writing problems. Non-creative writers also engage in creative writing analysis, to discover more about a completed work of writing, to place it in the context of a culture or society, a moment in history or a particular writing genre or form or tradition. Creative Writing Analysis details the many ways in which creative writing can be examined. Whether you are a creative writer seeking to improve your work or you are simply interested in analyzing the practice and outcomes of others doing creative writing, Creative Writing Analysis offers strategies to assist you. The book also includes a wonderfully supportive Afterword by Dianne Donnelly, whose work in Creative Writing Studies has been widely recognized as a contribution to the critical study of creative writing"--Provided by publisher.